2019
DOI: 10.1021/acschemneuro.9b00067
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of δ Opioid Receptor Full Inverse Agonists and Their Effects on Restraint Stress-Induced Cognitive Impairment in Mice

Abstract: The cyclopropylmethyl group in classical δ opioid receptor (DOR) antagonist NTI, BNTX, and NTB was replaced with various electron-withdrawing groups to develop DOR inverse agonists. N-Benzyl NTB derivative SYK-657 was a potent DOR full inverse agonist and its potency was over 10-fold potent than that of a reference compound ICI-174,864. Intraperitoneal administration of SYK-657 induced the short-term memory improving effect in mice without abnormal behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…As noted in the Introduction, a limited set of DOR irreversible antagonists and inverse agonists has been discovered and reported [5,6,[8][9][10][11][12][13][14]21,22]. The ligands we report here were developed from a novel naltrexone scaffold and thus represent a significant contribution to the limited set of pharmacological tools available to probe the DOR.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the Introduction, a limited set of DOR irreversible antagonists and inverse agonists has been discovered and reported [5,6,[8][9][10][11][12][13][14]21,22]. The ligands we report here were developed from a novel naltrexone scaffold and thus represent a significant contribution to the limited set of pharmacological tools available to probe the DOR.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 7 [ 24 , 25 ], which is the key intermediate for the synthesis of the target sulfonamide-type NTI derivatives, was synthesized from naltrexone hydrochloride ( 1 ) ( Scheme 1 ). Fischer indolization of 1 with phenylhydrazine hydrochloride gave NTI ( 2 ) [ 27 , 28 ] in 99% yield, which was treated with acetic anhydride to afford diacetate 3 in 95% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the key intermediate 7 was prepared by introduction of TBS group at the phenolic hydroxy group of 5 . Although we previously reported the synthesis of 7 from 1 [ 24 ], the synthetic method shown in Scheme 1 was four steps shorter and provided the key intermediate 7 in higher total yield than the previous method (see the Supporting Information for details). Portoghese et al and Rice et al independently reported the synthesis of the 5 hydrochloride from noroxymorphone in one step (see the Supporting Information for details) [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations